2020
DOI: 10.1097/md.0000000000019628
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of biomarkers for prostate cancer based on weighted gene co-expression network analysis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…This is consistent with our results, and we also found that MYH11 expression was lower in the high-risk group. Abnormal expression of ACTG2 has been found in many cancers, such as ACTG2 involved in cell migration and distant metastasis in liver cancer [19]. Our results found that the expression of ACTG2 was lower in the high-risk group of patients.…”
Section: Discussionsupporting
confidence: 49%
“…This is consistent with our results, and we also found that MYH11 expression was lower in the high-risk group. Abnormal expression of ACTG2 has been found in many cancers, such as ACTG2 involved in cell migration and distant metastasis in liver cancer [19]. Our results found that the expression of ACTG2 was lower in the high-risk group of patients.…”
Section: Discussionsupporting
confidence: 49%
“…We finally established the PPI network (Fig. 3 a) through the STRING online tool and Cytoscape [ 21 ]. The network provides a clear and direct expression of complex interactions between gene node, and many domain analyses are based on network analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This technology allows the use of function-specific mRNAs panels for simultaneous evaluations of cellular pathways and processes. On this light, we have used the PanCancer Progression Panel to perform multiplex gene expression analysis with 770 genes that are involved in each step of cancer progression, including angiogenesis, extracellular matrix remodeling (ECM), epithelial-to-mesenchymal transition (EMT) and metastasis [ 33 ]. From the analysis of the results a reduction of the metastatic response of the cells transduced with mimic miR-423-5p is recorded (Fig.…”
Section: Resultsmentioning
confidence: 99%